2013
DOI: 10.1155/2013/217695
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Magnifying Endoscopy with Narrow-Band Imaging for Determining Tumor Invasion Depth in Early Gastric Cancer

Abstract: Backgrounds. Magnifying endoscopy with narrow-band imaging (ME-NBI) has become essential for determining tumor margin in early gastric cancer (EGC). Here, we investigated the usefulness of ME-NBI for assessment of invasion depth in EGC. Methods. For 119 patients who had undergone ME-NBI and en bloc resection by endoscopic submucosal dissection, three physicians prospectively examined high-magnification ME-NBI images for clinical features such as presence or absence of dilated vessels (D vessels). Cases with D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 12 publications
1
23
0
Order By: Relevance
“…Studies were excluded if they were not original reports on the diagnosis of EGC or if they were case reports. After this filtering, 66 articles were selected for use in this algorithm (57 from PubMed and nine from the manual search) …”
Section: Methodsmentioning
confidence: 99%
“…Studies were excluded if they were not original reports on the diagnosis of EGC or if they were case reports. After this filtering, 66 articles were selected for use in this algorithm (57 from PubMed and nine from the manual search) …”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, its diagnostic ability is similar to that of CE alone [15][16][17], and a number of studies have stated that EUS is unsuitable as a routine investigation for determining the depth of invasion by EGCs [15]. In recent years, there have been some promising reports regarding the determination of invasion depth using new modalities such as infrared endoscopy [18] and magnifying endoscopy with narrow-band imaging [19], but these are yet to produce consistently reliable results.…”
Section: Discussionmentioning
confidence: 99%
“…In the first study by Kobara et al[63] it was concluded that the presence of non-structure, scattery vessels and multi-caliber vessels can possibly serve as indicators of SM2 invasion in differentiated-type of EGC. In the second study by Kikuchi et al[64] M-NBI images were examined for dilated vessels (D-vessels) which were defined as vessels with diameter 3 times larger than that of the irregular microvessels. The sensitivity and specificity of D-vessels for SM2 invasion were 37.5% and 88.3% respectively.…”
Section: Narrow Band Imagingmentioning
confidence: 99%